El auditor de sistemas y su participación en el outsourcing de procesos informáticos - Andrade Mejia, Jimmy (2009)
Although at the present time the use of the external hiring in many activities was suppressed also we know that the same one in functions stays that are not own of the institution that contracts it, one of these activities is indeed the one of the handling of computer science systems. This work I am made with a single purpose, the one to be able to lend a guide adapted of how an Auditor of Systems must assume his roll, a guide who concludes in a manual of the steps to follow at the time of contracting external services of the handling of the computer science systems for a company, to obtain from this hiring the wished result, defining clearly by means of policies, risks and methods of control to consider itself within the contract of outsourcing. The manual which this is the resultant of all the work based on control norms and focused international standards by all means to outsourcing computer science, mainly in Norms ISO 17799 and extracting certain points of consideration of other Norms like COBIT and similars.